Early Recurrence Adenoid Cystic Carcinoma of Paranasal Sinus, A Case Report - Marzaini, MD, Nikrial Dewin; Yossarsongko, Handoko Nugroho; Rayhani, Farilaila; Soeis, Dewi Syafriyetti (http://dharmais.co.id/, 2024)
Introduction: Adenoid cystic carcinoma (ACC) of the head and neck is a rare salivary gland tumor. It grows and spreads in silence until causing a symptom. Surgery is still the main treatment of choice although complete resection is hard to achieve most of the time. Case Presentation: This report presents an adult female with ACC of the left hard palate and left maxillary sinus, this patient also had slight lymph nodes enlargement. She underwent sub-total maxillectomy followed by locoregional radiotherapy. The tumor spreads out to vertebral bones within one year and keeps on progressing despite bone radiation. It recurred locally and appeared in the neck lymph node 2 months after bone metastasis. Lung metastasis happened 3 months later and soon she passed away. Mortality happened in less than two years after initial treatment. Conclusion: : High tumor grade, advanced T stage, lymph node involvement, perineural invasion, and paranasal sinus location clearly define poor prognostic factors. In this case, adjuvant radiotherapy for poor prognostic factors ACC doesn’t give any benefit in locoregional control or overall survival.